Pengelolaan Baitul Maal Dalam Meningkatkan Kesejahteraan Negara - Herlina Kusuma Wardani; Muhammad Tho'in (Jurnal Akuntansi dan Pajak, 2013)
The purpose of this research is to know how the management of Baitul Maal Masa Khulafaur Rashidin. The method used in this research is by using research that comes from literature study. The results showed that the management of Baitul Maal during the time of the Caliph Abu Bakr originally served only to distribute the treasures alone, but in the second year of his leadership also serves as a place to store various wealth owned by the state. Baitul maal is used to finance the interests of the state and the welfare of its people. At the time of Umar bin Khatab being the caliph of Abu Bakr after his death, the wealth or treasury owned by the state in the baitul maal increased very significantly, as much of the flow of funds from the conquered countries such as Kisra and Qaishar. At the time of the Caliph Usman bin Affan, the wealth of the country more abundant when compared with the two previous Caliphs. Where the area is conquered more so that the state treasury more and more, so that the country is getting stronger and prosperous, even baitul maal when his government is able to finance the navy that controls the Mediterranean Sea. Caliph Ali bin Abi Talib budgeted funds used to help the Muslims in need of help, even he did not want to take money from the baitul maal during a dispute between himself and the Muawiyah.